PENGARUH PENERAPAN METODE AUDIOLINGUAL UNTUK PENINGKATAN KETERAMPILAN BERBAHASA ARAB SISWA MTs MUHAMMADIYAH LIMBUNG - Fatmawati Fatmawati (Universitas Muhammadiyah Makassar, 2017)
The purpose of this study is to determine the effect of audiolingual method (atthoriqah assam'iyah assyafawiyah) in improving the Arabic skill of grade VIII students of MTs Muhammadiyah Limbung. This research is a field research by using qualitative descriptive method, with data source of one teacher of Arabic study and 66 students of MTs Muhammadiyah Limbung. The method of collecting research data was observation, questionnaire and interview. The results of this study indicated that (1) the application of audiolingual method on learning Arabic based on questionnaire was known that 56 or 84,84% which become sample of answer research had been applied, while 9 or 13,63% answer enough applied, and 1 or 1,51 % who answered less applied, while the answer is not applied 0 or 0%. (2) students' Arabic skill based on questionnaire shows that 35 people or 53,03% answer very good, 30 people or 45,45% 1 person or 1.51% who responded poorly and 0% or none responded unfavorably (3) the influence of the application of audiolingual method (al thoriqah al sam'iyah al syafawiyah) for the improvement of Arabic skill. Of the respondents who said strongly affects 38 people or 57.57%, who say enough 26 people or 39.39% of them who say less affect 2 people or 3.03% while no one answered no effect.